A Role for Malignant Brain Tumor Domain-Containing Protein 1 in Human Endometrial Stromal Cell Decidualization - Chadchan, Sangappa B.; Maurya, Vineet K.; Krekeler, Gwendalyn L.; Jungheim, Emily S.; Kommagani, Ramakrishna (Frontiers in Cell and Developmental Biology, 2020)
Up to 30% of women experience early miscarriage due to impaired decidualization. For implantation to occur, the uterine endometrial stromal fibroblast-like cells must differentiate into decidual cells, but the genes required for decidualization have not been fully defined. Here, we show that Malignant Brain Tumor Domain-containing Protein 1 (MBTD1), a member of the polycomb group protein family, is critical for human endometrial stromal cell (HESC) decidualization. MBTD1 predominantly localized to human endometrial stromal cells during the secretory phase and the levels were significantly elevated during in vitro decidualization of both immortalized and primary HESCs. Importantly, siRNA-mediated MBTD1 knockdown significantly impaired in vitro decidualization of both immortalized and primary HESCs, as evidenced by reduced expression of the decidualization markers PRL and IGFBP1. Further, knockdown of MBTD1 reduced cell proliferation and resulted in G2/M cell cycle arrest in decidualizing HESCs. Although progesterone signaling is required for decidualization, MBTD1 expression was not affected by progesterone signaling, however MBTD1 knockdown significantly reduced expression of the progesterone target genes WNT4, FOXOA1, and GREB1. Collectively, our data suggest that MBTD1 contributes to in vitro decidualization of HESCs by sustaining progesterone signaling. This work could have implications for designing diagnostic and therapeutic tools for recurrent pregnancy loss.